Enhancing computational thinking in students with autism spectrum disorder and intellectual disabilities: a robot programming approach. - Kim, MiJeong; Kim, JaMee; Lee, WonGyu (International Journal of Developmental Disabilities, 2026)
Objectives: Research examining computational thinking skills development via programming education using robotic teaching tools for students with Autism Spectrum Disorder and Intellectual Disabilities remains limited. This study aims to analyze the advancements in computational thinking skills among middle school students with Autism Spectrum Disorder and Intellectual Disabilities through participation in robot programming classes. Methods: Problem-solving proficiency in computational thinking was assessed utilizing Brennan and Resnick's three dimensions framework. A tailored teaching and learning approach was implemented for robot programming education, accounting for participants' cognitive abilities and required levels of support. Four middle school students, comprising one with Autism Spectrum Disorder and three with Intellectual Disabilities, were enrolled. Results: Significant enhancements were observed in all participants' computational thinking skills across conceptual understanding, practical application, and perspective. Notably, all participants successfully resolved the final project problem at their individual proficiency levels. The acquisition of computational concepts was found to correlate positively with improved practical computational skills. Additionally, all participants demonstrated keen interest in and positive attitudes toward both robots and programming. Conclusions: This study underscores the efficacy of robotic teaching tools in enhancing computational thinking skills through programming education. Additionally, it highlights considerations for enhancing students' accessibility in future programming class design.